An Internet-based cognitive behavioral therapy for treatment-induced menopausal symptoms in breast cancer survivors: results of a pilot study. Issue 7 (July 2017) - Atema, Vera; van Leeuwen, Marieke; Oldenburg, Hester S.A.; van Beurden, Marc; Hunter, Myra S.; Aaronson, Neil K.
Abstract: Objective: Previous studies demonstrated that a cognitive behavioral therapy (CBT) program delivered in group sessions is effective in alleviating treatment-induced menopausal symptoms in women with breast cancer, but also that in-person CBT is inconvenient for some women and can result in low levels of program compliance. A promising, alternative approach is to use the Internet to make this form of CBT more accessible and feasible for patients. The objective of this study was to evaluate the feasibility and to generate preliminary data on the efficacy of a guided, Internet-based CBT program. Methods: Twenty-one participants with treatment-induced menopausal symptoms started the guided Internet-based CBT program. Self-report questionnaires were completed at baseline and at 10 weeks (posttreatment). Counselors' evaluations were obtained via interviews. Primary outcomes were program usage, compliance rates, and participant and counselor satisfaction. Secondary outcomes were overall levels of endocrine symptoms and hot flush/night sweats problem rating. Results: Ninety percent of participants completed the program as planned. Satisfaction rates were high among participants and counselors. Small revisions to the program were advised. There was a significant decrease over time in overall levels of endocrine symptoms and hot flush/night sweats problem rating. Conclusions: These findings suggest that an Internet-based CBT program for women with treatment-induced menopausal symptoms is feasible and promising in terms of efficacy. The efficacy of the CBT program is currently being investigated in a larger randomized controlled trial.